Dynamic investigation of defects induced by short, high current pulses of high energy lithium ions. Issue 1712 (8th September 2014) - Guo, Hua; Persaud, Arun; Lidia, Steve; Minor, Andrew M.; Hosemann, P.; Seidl, Peter A.; Schenkel, Thomas
ABSTRACT: We employ intense and short pulses of energetic lithium (Li + ) ions to investigate the relaxation dynamics of radiation induced defects in single crystal silicon samples. Ions both create damage and track damage evolution simultaneously at short time scales when we use the channeling effect as a diagnostic tool. Ion pulses, ∼20 to 600 ns long and with peak currents of up to ∼1 A are formed in an induction type linear accelerator, the Neutralized Drift Compression eXperiment at Lawrence Berkeley National Laboratory. By rotating silicon (<100>) membranes of different thicknesses and changing the incident ion energy, the fraction of channeled ions in the transmitted beam could be varied. In preliminary experiments we find that the Li ion intensity is not high enough to generate overlapping cascades (in time and space) that would be necessary to measure a change in the shape of the current waveform of the transmitted ion beam. We discuss the concept of pump-probe type experiments with short ion beam pulses to access defect dynamics in materials and outline a path to increasing damage rates with heavier ions and by the application of longitudinal and lateral pulse compression techniques.